A neuropedagogia no processo de ensino e aprendizagem: uma abordagem da neurociência aplicada à educação no ensino fundamental I - SILVA, Danielle Ferreira da (Universidade Federal do Tocantins, 2021)
Neuropedagogy studies how the human brain learns and stores this learning. Thus, this study aims to understand the role of Neuropedagogy, an area of neuroscience applied to education, as a fundamental science in teacher education. This is a literature review. The survey of scientific data and the systematization of information come from books and other scientific production published from 2010 to 2020 in the Portuguese language, indexed in several databases, focusing on the concepts of Neuropedagogy, teacher training and the teaching and learning process. Neuropedagogy is the junction between neuroscience and education, two distinct scientific fields, but united and adapted to contemporary pedagogy. Within the classroom there is a conglomerate of people who have distinct configurations in their brain biology, endowed with particularities. Neuroscience has vast content to assist the teacher in the teaching-learning process, its branch, Neuropedagogy, becomes a scientific field of great relevance for integration in the teacher education curriculum. The teacher endowed with knowledge from neuroscience, especially Neuropedagogy, can arouse students' interest in learning, activating their emotions, such as affection and pleasure, while this professional helps in the production of neurotransmitters such as serotonin and dopamine. It can be concluded that the dialogue that Neuropedagogy establishes with neuroscience brings a set of knowledge about the brain functionalities that are essential to understand students' learning difficulties, especially children, because they receive constant information in their training process. student and human, so that their brain masses deserve attention because they are in constant changes and transformations due to the new knowledge acquired in this childhood stage of life.